INDONESIAN STUDENTS’ PERSPECTIVES ON ELT IN SHADOW EDUCATION - Qurrotul Aini S; Kristian Adi Putra (The Journal Of English Teaching For Young And Adult Learners, 2023)
The demand for shadow education in Indonesia is continuously increasing, raising the doubts on the quality of teaching at schools. Therefore, this study aims at analyzing students’ perceptions particularly on English language teaching in shadow education, as compared to those at schools. This study uses semi-structured individual interviews to obtain rich data on students’ experiences and perceptions. The participants were secondary level students who were well-experienced in English shadow education program. The result of this study showed that students’ perception of shadow teaching covered several aspects such as teaching materials, learning outcome, teaching activities, teachers’ teaching performance and learning media. Practically, the students’ perspective towards shadow education had an average of positive experiences. Furthermore, the implications of present study call for a sense of urgency among policy makers and education authorities to consider curricular and methodological overhauling to enhance English teaching efficiency and students’ learning outcomes in line with students’ needs, preferences and concerns in shadow teaching.